2016
DOI: 10.2340/00015555-2205
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy for Actinic Keratoses: A Randomized Prospective Non-sponsored Cost-effectiveness Study of Daylight-mediated Treatment Compared with Light-emitting Diode Treatment

Abstract: Daylight-mediated photodynamic therapy (DL-PDT) is considered as effective as conventional PDT using artificial light (light-emitting diode (LED)-PDT) for treatment of actinic keratoses (AK). This randomized prospective non-sponsored study assessed the cost-effectiveness of DL-PDT compared with LED-PDT. Seventy patients with 210 AKs were randomized to DL-PDT or LED-PDT groups. Effectiveness was assessed at 6 months. The costs included societal costs and private costs, including the time patients spent in treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The higher the score, the stronger the pain intensity. Pooled data across all eight studies, comprising 424 patients, revealed a lower level of pain in the patients who underwent DLPDT than in those who underwent CPDT ( n = 424; SMD, −2.544; 95% CI, −3.57 to −1.632; P < 0.001; Fig. ), suggesting a positive effect associated with DLPDT treatment of AKs with respect to pain.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…The higher the score, the stronger the pain intensity. Pooled data across all eight studies, comprising 424 patients, revealed a lower level of pain in the patients who underwent DLPDT than in those who underwent CPDT ( n = 424; SMD, −2.544; 95% CI, −3.57 to −1.632; P < 0.001; Fig. ), suggesting a positive effect associated with DLPDT treatment of AKs with respect to pain.…”
Section: Resultsmentioning
confidence: 96%
“…Next, we read the entire texts of the remaining 22 studies in detail, of which 14 were discarded because they lacked the required outcome, contained duplicate data, or had not employed a test for randomness. Finally, eight articles comprising 424 patients were found to be suitable for this meta‐analysis and bias analysis . A flow diagram of our search strategy is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations